Orders of Hunger and Heaven: Neoliberalism, Christian Charity and Homelessness in Taiwan - Beck, Scott R. (Religions, 2021)
Based on an ethnographic study of a Christian charity in Taipei, Taiwan, this paper examines how the mixing of “orders of worth” (Boltanski and Thevenot) is negotiated among charity workers and homeless people in the field setting. The organization, Grace Home Church, has two official goals: (1) to glorify God; (2) to assist homeless people. This mix of sacred and secular purposes often produces tensions, with the fundamental tension being between what the charity seeks to provide (salvation) versus what the homeless commonly want to be provided (food). As an analytic tool, I utilize Boltanski and Thevenot’s framework to link emergent tensions with broader social forces, such as neoliberalism, the welfare state, and religion. I will argue that charity workers as well as homeless individuals who have accepted Christianity attempt to separate the market and inspired orders through signifying practices that maintain a symbolic order, thereby justifying a sacred mission (for the charity organization) and self-worth (for the homeless).